Association of anti-CLIC2 and anti-HMGB1 autoantibodies with higher disease activity in systemic lupus erythematosus patients - CS, Syahidatulamali; WG, Wan Syamimee; Y, Nor Azwany; Wong, KK; CH, Che Maraina (Medknow Publications, 2017)
Systemic lupus erythematosus (SLE) is a systemic autoimmune disease characterized by numerous autoantibodies. In this study, we investigated the presence of anti-chloride intracellular channel 2 (anti-CLIC2) and anti-high mobility group box 1 (anti-HMGB1) autoantibodies in SLE patients (n = 43) versus healthy controls ([HCs] n = 43), and their association with serological parameters (antinuclear antibody [ANA], anti-double-stranded DNA [anti-dsDNA], and C-reactive protein [CRP]) and disease activity using Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score (active or inactive). Settings and Design: Case– control study at Rheumatology Clinic of Universiti Sains Malaysia Hospital. Subjects and Methods: The sera of SLE patients and HCs were tested for the presence of anti-CLIC2 and anti-HMGB1 autoantibodies using human recombinant proteins and ELISA methodologies. Other serological parameters were evaluated according to routine procedures, and patients' demographic and clinical data were obtained. Statistical Analysis: Mann– Whitney U-test, Chi-square test, Fisher's exact test, and receiver operating characteristic analysis. Results: Anti-CLIC2 autoantibody levels were significantly higher in SLE patients compared to HCs (P = 0.0035), whereas anti-HMGB1 autoantibody levels were not significantly elevated (P = 0.7702). Anti-CLIC2 and anti-HMGB1 autoantibody levels were not associated with ANA pattern, anti-dsDNA, and CRP. Interestingly, SLEDAI score (≥6) was associated with anti-CLIC2 (P = 0.0046) and with anti-HMGB1 (P = 0.0091) autoantibody levels. Conclusion: Our findings support the potential of using anti-CLIC2 autoantibodies as a novel biomarker for SLE patients. Both anti-CLIC2 and anti-HMGB1 autoantibody levels demonstrated potential in monitoring SLE disease activity.